2022
DOI: 10.3389/fnut.2022.955846
|View full text |Cite
|
Sign up to set email alerts
|

Producing natural functional and low-carbon milk by regulating the diet of the cattle—The fatty acid associated rumen fermentation, biohydrogenation, and microorganism response

Abstract: Conjugated linoleic acid (CLA) has drawn significant attention in the last two decades for its various potent beneficial effects on human health, such as anticarcinogenic and antidiabetic properties. CLA could be generally found in ruminant products, such as milk. The amount of CLA in ruminant products mainly depends on the diet of the animals. In general, the fat content in the ruminant diet is low, and dietary fat supplementation can be provided to improve rumen activity and the fatty acid (FA) profile of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 199 publications
1
6
0
Order By: Relevance
“…Onetti et al [ 24 ] reported that supplementing animal fats to corn silage increased the proportion of propionate in Holstein cows. These findings were consistent with a meta-analysis and review paper by Patra [ 11 ] and Sun et al [ 25 ], which reported that increasing dietary fat levels were associated with increased propionate and decreased butyrate and the A:P ratio. Unsaturated fatty acids in the fat content of the feed decrease the populations of methanogens and protozoa in the rumen [ 26 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Onetti et al [ 24 ] reported that supplementing animal fats to corn silage increased the proportion of propionate in Holstein cows. These findings were consistent with a meta-analysis and review paper by Patra [ 11 ] and Sun et al [ 25 ], which reported that increasing dietary fat levels were associated with increased propionate and decreased butyrate and the A:P ratio. Unsaturated fatty acids in the fat content of the feed decrease the populations of methanogens and protozoa in the rumen [ 26 ].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, as higher fat levels led to increased propionate production, it is likely that H 2 in the rumen was primarily utilized for propionate production rather than for the biohydrogenation of UFAs. Sun et al [ 25 ] have suggested that due to the limited availability of H 2 for the biohydrogenation of UFAs in the rumen, the primary influence of dietary fat on CH 4 emissions would likely be its direct impact on methanogens and rumen microbial population.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, methane production did not decrease with the increase in protected PA. The lack of effect is because it is a SFA, and it cannot capture H 2 ions through the biohydrogenation process (Sun et al 2022). The data from this study indicate that diets with SFA such as protected PA do not have total protection; part of the PA is available and used by rumen microorganisms and has an effect of decreasing the GP and consequently decreases the degradability of DM and OM (Buccioni et al 2012).…”
Section: Discussionmentioning
confidence: 85%
“…Consequently, numerous studies have focused on enhancing the value of animal products, particularly by increasing the concentration of FAs in milk and dairy products that have favorable effects on human health [13][14][15][16][17]. From a nutritional perspective, a more favorable FA profile would entail a reduced proportion of SFAs and an increased proportion of UFAs, with particular focus on n-3 PUFAs, along with a lower n-6/n-3 ratio [18].…”
Section: Introductionmentioning
confidence: 99%